A educação ambiental como objeto de estudos nos programas stricto sensu em turismo no Brasil (período 1997-2011) - Denicol, Maria Salete Goulart Martins (My University, 2014)
The Environmental Education (EE) is an important instrument to sustainable tourism development, being used to people sensitization about environmental impacts minimization resulting from the use of natural resources in touristic activities. In this perspective, studies about EE in Tourism Stricto Sensu Postgraduation Programs in Brazil seem to be important and necessary to identify trends and gaps in the knowledge production process. From some indagations arises the research problem: How the Environmental Education theme has been studied in Tourism Stricto Sensu Programs dissertations in Brazil? Therein it intends itself to map as EE is contemplated about knowledge production in dissertations of these Programs, recognized and recommended by Capes from 1997 to 2011. The research is descriptiveness with qualitative/quantitative approach and it consists in the dissertations analysis that present the “Environmental Education” exact expression in its abstracts developed in the Tourism Stricto Sensu Postgraduation Programs, constants at Capes’ Database. Therefore, it was in use the search of type “art state”, to aid in the investigation, the obtained results from the research conclude that from the Tourism Stricto Sensu Postgraduation six Programs in Brazil, they identified ten dissertations with the “Environmental Education” exact expression contained in the title, either abstract or keywords, being Vale do Itajaí University’s Tourism and Hotelaria Master’s Degree Program five dissertations and Caxias do Sul University’s Tourism Master’s Degree Program five dissertations. After reading the works, from methodological view-point, it was observed that only five dissertations present, the EE as studies object, being the effected researches at country south region. They become evident gaps that are relative to four Tourism Postgraduation Programs, in which they were not identified dissertations with the “Environmental Education” exact expression. At last, it becomes important to suggest the researches development to deepen and provoke reflections, in order to evidence in Tourism Stricto Sensu Postgraduation Programs in Brazil, the scientific research about EE.
A Educação Ambiental (EA) é uma importante ferramenta para o desenvolvimento do turismo sustentável, sendo utilizada na sensibilização das pessoas sobre a minimização dos impactos ambientais, decorrentes do uso de recursos naturais nas atividades turísticas. Nessa perspectiva, estudos sobre a EA nos Programas de Pós- Graduação Stricto Sensu em Turismo, no Brasil, parecem ser importantes e necessários para identificar tendências e lacunas no processo de produção de conhecimento. Partindo de algumas indagações surge o problema de pesquisa: Como o tema Educação Ambiental vem sendo estudado nas dissertações dos Programas Stricto Sensu em Turismo no Brasil? Neste sentido, objetiva-se mapear como a Educação Ambiental é contemplada na produção do conhecimento nas dissertações desses Programas, reconhecidos e recomendados pela Capes no período de 1997 a 2011. A pesquisa é de caráter descritivo com abordagem qualitativa/quantitativa e consiste na análise das dissertações que apresentam a expressão exata Educação Ambiental nos seus resumos, desenvolvidas nos Programas de Pós-Graduação Stricto Sensu em Turismo, constantes no Banco de Teses da Capes. Para tal, utilizou-se a pesquisa do tipo “estado da arte”, para auxiliar na investigação. Os resultados obtidos com a pesquisa permitem concluir que, dos seis Programas de Pós-Graduação Stricto Sensu em Turismo no Brasil, identificaram-se 10 dissertações com a expressão exata Educação Ambiental contida no título, ou no resumo ou em palavras-chave, sendo cinco dissertações do Programa de Mestrado em Turismo e Hotelaria, da Universidade do Vale do Itajaí e cinco dissertações do Programa de Mestrado em Turismo da Universidade de Caxias do Sul. Após a leitura dos trabalhos na íntegra, observou-se que apenas cinco dissertações apresentam, do ponto de vista metodológico, a EA como objeto de estudos, sendo as pesquisas realizadas na Região Sul do País. Evidenciam-se lacunas no que tange a quatro Programas de Pós-Graduação em Turismo, nas quais não foram identificadas dissertações com a palavra exata Educação Ambiental. Por fim, torna-se importante sugerir o desenvolvimento de pesquisas para aprofundar e provocar reflexões, no sentido de evidenciar, nos Programas de Pós-Graduação Stricto Sensu em Turismo, no Brasil, a investigação científica em Educação Ambiental.
Keywords: Turismo; Turismo - Metodologia; Educação ambiental; Pesquisa - Metodologia; Ensino superior - Pós-graduação